VARIASI BAHASA WHATSAPP MAHASISWA MAGISTER BAHASA INDONESIA UNIVERSITAS MATARAM 2021 - Atmanegara, Lalu Kusnendar; Sukri, Muhammad; Burhanuddin, Burhanuddin (Lembaga Penelitian dan Pendidikan Mandala, 2022)
The research with the title Whatsapp Language Variations for Indonesian Masters Students at the University of Mataram aimed to find out the variations of the language used in conducting written communication through social media in the form of a Whatsapp account. This research was a qualitative type. The data in this study were the results of Whatsapp conversations and the data source was from student Whatsapp conversations. The data collection by observation and Screenshoot messages that entered in Whatsapp group and analyzing by collected the messages from Whatsapp, entered data into language variations, and made conclusions. The results showed that there were three variations of the language used: acronyms,slang and code mixing. Thus, it can be said that the use of language variations is caused by different backgrounds, mastery of language, as well as social factors and the desire to follow language developments.